The Effect of Socioeconomic Factors on Outcomes of Distal Radius Fractures: A Systematic Review. (September 2018) - Truong, Jessica L.; Doherty, Chris; Suh, Nina
Background: Socioeconomic factors are known to affect outcomes for both medical and surgical conditions. The purpose of this systematic review was to assess the current evidence regarding the effect of socioeconomic factors such as income, geographic location, educational level, and occupation on clinical outcomes after distal radius fractures.Methods: A systematic search strategy was performed to identify studies commenting on the effect of socioeconomic factors on clinical outcomes following open or closed distal radius fracture repair. Abstract and full-text screening was performed by 2 independent reviewers, and articles were evaluated by Structured Effectiveness Quality Evaluation Scale (SEQES). Treatment outcomes of interest included, but were not limited to, pain, function, range of motion, and grip strength.Results: There were 1745 studies that met our inclusion and exclusion criteria for abstract screening. Of these, 48 studies met our inclusion criteria for full-text screening and 20 studies met our criteria for quality analysis with the SEQES score. There were 3 studies of high quality, 16 of moderate quality, and 1 of low quality. Meta-analyses were not possible due to the variability in outcomes of interest across papers.Conclusions: Patient factors indicative of socioeconomic status are relevant predictors of functional outcome after distal radius fractures. There is currently limited evidence in this area of research, and further examination should be considered to improve outcomes from a patient and system standpoint.